Growth and yield of native germplasm of large cardamom in the wild habitat of Arunachal Pradesh - Yadav, A K Dubey, D S (Journal of Spices and Aromatic Crops, 2002)
Surveys were made during 1998 and 1999 to identify and evaluate in situ the germplasm of large cardamom available in natural forests of Arunachal Pradesh. It was observed that eight distinct types of large cardamom were present in this state, which differ significantly in their morphological characteristics. Boklok, a high altitude accession, had the highest plant height, number of tillers and panicles, maximum yield and dry weight of fruits. However, fruits panic1e-t was found· to be highest in Bebo light red. Jaker green has larger capsules with highest fresh weight of fruits, while Belak had the highest number of seeds fruirl. The germplasm collected provides good scope for the crop improvement through breeding.